PENGARUH KOMITMEN ORGANISASI DAN KOMPENSASI TERHADAP KINERJA PERSONIL BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT (BHABINKAMTIBMAS) DI POLRESTA BANJARMASIN - Arif Wahyu Bibiharta; Ahmad Alim Bachri; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
This study analyzes the influence of organizational commitment and compensation simultaneously on the performance of personnel BHABINKAMTIBMAS Polresta Banjarmasin, analyzing the influence of organizational commitment and partial compensation to personnel performance BHABINKAMTIBMAS Polresta Banjarmasin, analyzing the dominant variable of organizational commitment and compensation affecting BHABINKAMTIBMAS Polresta Banjarmasin performance. The research method used is explanatory research with quantitative approach. The population of this research was 52 people with purposive sampling sampling technique with 52 samples. data collection was done by using questionnaire. Data analysis using multiple regression with F test and t test. The Influence of Organizational Commitments (X1) affects the performance of personnel (Y). The proof of the statement can not be based on the value of t greater than the value of t table (4.824> 2.007) and lower value significantly than error rate (0,000 <0,05). The effect of Work Compensation (X2) influenced the performance of personnel (Y) of t table (3.931> 2.007) and significantly lower value than error rate (0,000 <0,05). This result shows that partial compensation work variable has an effect on personnel performance. The table above shows that 0.942 = 94.2% means there are still other variables that affect the personnel performance besides the organizational commitment variable and the simultaneous commitment to the personnel performance of BHABINKAMTIBMAS Polresta Banjarmasin.